(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Background: The associations between elevated blood pressure and overweight increasing now a days. Over the last few decades the prevalence of elevated blood pressure also increased in children due to increasing pediatric overweight because of changing dietary habits, changing pattern of life style. Objective: To see the body mass index and waist hip ratio a predictor of hypertension of adolescent boys and girls in a metropolitan city in Bangladesh. Methods and Materials: This cross-sectional– descriptive study was conducted in the department of Pediatrics, Sylhet M.A.G. Osmani Medical College Hospital, Sylhet during the period from January 2014 to June 2014. Adolescent boys and girls in Sylhet Metropolitan City were included according to inclusion and exclusion criteria. Inclusion criteria were children aged 12-16 years in Sylhet Metropolitan City. Children aged under 12 or above 16 years and with any systemic disorder were excluded. Results: This study showed that 56.4% adolescents were male and 43.6% were female with ratio of male: female = 1.3:1 and their average age was 14±2 yrs. Average height of male was 154.82±49.08 cm and female was 148.42±38.09 cm. Average weight of male was 49.12±10.49 kg and that of female was 44.48±12.08 kg .Prevalence of hypertension in adolescent boys and girls of Sylhet city was 0.70% and there was a significant relationship of hypertension with the obesity. Among 7 (seven) hypertensive children, 3(42.8%) were overweight and 3(42.8%) obese (p=0.001). While waist hip ratio among those, 2(28.6%) were excellent and 5(71.4%) were average; was not significant (p=0.745) among the hypertensive adolescents. Conclusion: Prevalence of hypertension in apparently healthy adolescent child of Sylhet city was 0.70% and had a strong relationship with high body mass index J Bangladesh Coll Phys Surg 2020; 38(3): 110-115